2019
DOI: 10.1111/jfs.12723
|View full text |Cite
|
Sign up to set email alerts
|

Searching potential candidates for development of protective cultures: Evaluation of two Lactobacillus strains to reduce Listeria monocytogenes in artificially contaminated milk

Abstract: The aims of this work were (a) to select the minimum concentrations of two bacteriocin-producing lactobacilli strains to reduce Listeria monocytogenes growth in whole milk, (b) to evaluate the individual and combined application of these chosen lactobacilli concentrations as protective culture in this food and, (c) to estimate if lactobacilli growth caused undesirable changes in the visible characteristics of milk.The selected minimum lactobacilli concentration with antilisterial activity was 10 6 CFU ml −1 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Therefore, the use of the selected LAB as bioprotective starter cultures presents a valid way to prevent or limit the development of pathogens such as L. monocytogenes. L. monocytogenes was reduced in whole milk by different Lactobacillus strains (Garcia et al, 2019) and by Carnobacterium piscicola in refrigerated food (Campos et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of the selected LAB as bioprotective starter cultures presents a valid way to prevent or limit the development of pathogens such as L. monocytogenes. L. monocytogenes was reduced in whole milk by different Lactobacillus strains (Garcia et al, 2019) and by Carnobacterium piscicola in refrigerated food (Campos et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, short-chain fatty acids (SCFA), which are formed through microbial metabolite cross-feeding, suppress listeria growth and support the body's disease defense. The health-promoting bacteria also produce various substances that inhibit L. monocytogenes, such as bacteriocins [57][58][59][60][61][62][63][64]. The fact that L. monocytogenes is able to utilize beta(1,3)-D-glucan is therefore not alarming.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity observed during storage could be attributed to a reduction in pH values due to an increased production of lactic acid by LAB strains, but not solely, as demonstrated by the fact that in most samples pH values were identical to the control and there was little pH drop during cheese storage. Authors have shown the ability of LAB to compete with L. monocytogenes avoiding its growth (Arena et al, 2016;Campagnollo et al, 2018;García et al, 2020;Scatassa et al, 2017) and, given that dairy-associated strains of L. plantarum are able to produce bacteriocins active against L. monocytogenes (Hernandez et al, 2005;Panebianco et al, 2021), the synthesis of these compounds by LAB is the most likely explanation for the observed L. monocytogenes reduction (Coelho et al, 2014). Despite the fact that the kinetics of bacteriocin synthesis was not assessed in the current study, several authors report that bacteriocin production increases during the exponential phase of LAB growth and stabilizes during the stationary phase (Benkerroum et al, 2002;Han et al, 2013;Martínez et al, 2013).…”
Section: Articlementioning
confidence: 99%